2016
DOI: 10.1097/md.0000000000005432
|View full text |Cite
|
Sign up to set email alerts
|

Association between cigarette smoking and interleukin-17A expression in nasal tissues of patients with chronic rhinosinusitis and asthma

Abstract: Cigarette smoke plays a substantial role in the development of airway inflammatory diseases, including asthma and chronic rhinosinusitis (CRS). Interleukin (IL)-17A might contribute to cigarette smoke-related inflammation of the airway. This study aimed to investigate the association between cigarette smoking and IL-17A expression in the nasal tissues of patients with CRS and asthma.We prospectively recruited 24 patients (13 smokers, 11 nonsmokers) with CRS and asthma and 6 patients with asthma but without CRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 44 publications
(38 reference statements)
3
32
0
Order By: Relevance
“…In our previous study utilizing eosinophilic CRS murine models, smoking exposure enhanced eosinophilic infiltration and generated more severe polypoid remodelling with type 1, 2, and 3 responses up‐regulated . The CRS mucosal cytokine profile of smokers has been reported to be dominated type 3 mediators such as IL‐17A, CXCL‐8, and TNF‐ɑ in earlier studies . Dysregulated host defences such as reduced expression level of the polymeric immunoglobulin receptor, secretory leucocyte protease inhibitor, and the long and short palate, lung and nasal epithelium clone protein were observed when cigarette smoke was exposed .…”
Section: Discussionmentioning
confidence: 97%
“…In our previous study utilizing eosinophilic CRS murine models, smoking exposure enhanced eosinophilic infiltration and generated more severe polypoid remodelling with type 1, 2, and 3 responses up‐regulated . The CRS mucosal cytokine profile of smokers has been reported to be dominated type 3 mediators such as IL‐17A, CXCL‐8, and TNF‐ɑ in earlier studies . Dysregulated host defences such as reduced expression level of the polymeric immunoglobulin receptor, secretory leucocyte protease inhibitor, and the long and short palate, lung and nasal epithelium clone protein were observed when cigarette smoke was exposed .…”
Section: Discussionmentioning
confidence: 97%
“…[84][85][86][87][88] This process may be mediated by cytokines, as interleukin (IL)-6, IL-8, and IL-17A have all been implicated in n eutrophil chemotaxis in smokers with asthma. [85][86][87][88][89] In addition, smoking may induce CD8+ T cell proliferation in the asthmatic airway, 90 similar to COPD. 91 92 Studies have shown that both neutrophil and CD8+ T cell numbers correlate well with increasing airflow obstruction.…”
Section: Smokingmentioning
confidence: 99%
“…Also, IL17A serum levels can be influenced by periodontal disease and smoking status was not assessed in the present study. Although there is no evidence pointing to the influence of smoking on IL17A expression on oral tissues, it was significantly elevated in the bronchial mucosa of asthmatic smokers, supporting its role on the development of neutrophilic inflammation of the airways, characterising severe disease and acute asthma attacks (Huang et al., ; Siew, Wu, Ying, & Corrigan, ). Inasmuch, recent evidence suggests an increase in IL17A mRNA expression in OLP patients with periodontal disease (Linhartova et al., ).…”
Section: Discussionmentioning
confidence: 99%